Pengaruh Inovasi dan Literasi Bisnis Digital Terhadap Keunggulan Bersaing Pelaku UMKM Kuliner Rumahan yang Terdaftar di GoFood - Syofyan, Rita; Ananda Putri, Nia; Putra, Defriko Gusma; Hayati, Annur Fitri; Murdy, Khairi (Jurnal Ecogen, 2024)
This study aims to determine and analyze the influence of innovation and digital business literacy on the competitive advantage of home-based culinary SMEs registered by GoFood in Padang City. This type of research is an associative descriptive study. The population in this study are home-based culinary SMEs registered by GoFood in Padang City. The sample used was 75 SMEs using proportional non random sampling. The type of data in this study is primary data. Data processing uses SPSS22. The data collection technique used is a questionnaire. The data that has been collected was analyzed by descriptive analysis. This study uses multiple regression analysis.Based on the results of the study, it is known that innovation has a significant effect on the competitive advantage of home-based culinary MSME actors registered with GoFood in Padang City with a value of Sig 0.011<0.05, digital business literacy has a significant effect on the competitive advantage of home-based culinary MSME actors registered with GoFood in Padang City with Sig 0.002< 0.05, innovation and digital business literacy have a significant effect on the competitive advantage of home-based culinary SMEs registered by GoFood in Padang City with Sig 0.024 <0.05